Taxonomic study of Tanypodinae (Chironomidae: Diptera) larvae in Balloran River – Lattakia – Syria - Rajab, Eva (International Journal of Scientific Research in Biological Sciences, 2021)
Tanypodinae larvae samples were collected monthly from one fixed site in Balloran river (Lattakia, Syria) for a year, during the period from December 2017 till October 2018. Slides were prepared and morphological characteristics of last-instar larvae (matured) were used to determine the classification of species. As a result, Two species namely (Ablabesmya malloshi; Procladius bellus) were reported in the station.